Nikel Indonesia dan Fosfat Yordania: Analisis Sinergi Strategis dan Komparasi Dampak Sektoral Terhadap Ekonomi, Lingkungan, Serta Pasar Modal Syariah dan Uang - Mutiara Kesuma; Maryam Batubara (Economic Reviews Journal, 2026)
This study analyzes the strategic synergy between Indonesian nickel and Jordanian phosphate commodities and compares the impact of both countries’ mining sectors on the economy, the environment, and the Islamic capital market. Using a qualitative approach with a multi-site comparative case study design, the study finds that Indonesia’s nickel downstreaming policy has driven substantial economic growth, with the mining sector contributing 12% of GDP in 2024 and processed nickel exports reaching USD9.73 billion in 2025. However, the policy faces serious criticism because of oversupply that has pushed nickel prices down by nearly 40%, from US$38,000 to US$15,000 per ton, extreme dependence on the Chinese market which absorbs 94% of downstream exports, and foreign dominance over roughly 75% of domestic nickel-refining capacity. The environmental impact is also severe, reflected in 5,501 hectares of deforestation, smelter CO2 emissions of 58.6 tons per ton of nickel, five times higher than Australia’s, and a surge in acute respiratory illness cases reaching 55,527. By contrast, Jordan’s phosphate industry, which contributes 25% of national manufacturing output, shows a more planned “green transformation” approach, although it still faces water-scarcity challenges. From a capital-market perspective, both commodities have been integrated into the Islamic financial ecosystem through sharia-indexed stocks and corporate sukuk, with Indonesia showing greater depth and diversity of instruments. The study’s main recommendation is to strengthen bilateral cooperation through existing joint ventures, apply Islamic-finance principles and environmental sustainability simultaneously, and diversify export markets and technology to reduce strategic vulnerability.